Rain May and Captain Daniel /Catherine Bateson. - Bateson, Catherine,1960-
Following her parents separation, twelve-year-old Rain moves with her mother to the country, where she befriends the unpopular boy who lives next door and also seeks a way to cope with her feelings toward her father and his new girlfriend.